PENGEMBANGAN SPIRIT KEWIRAUSAHAAN DAN KETERAMPILAN PEMASARAN DIGITAL ANAK MELALUI KIOS USAHA BERSAMA ANAK (KUBA) DI KAMPUNG BAKAT SURABAYA - Marlina, Maria Asumpta Evi; Yusup, Adi Kurniawan; Hendra, Hendra (Universitas Mataram, 2025)
The child entrepreneurship mentoring program through Kios Usaha Bersama Anak (KuBA) at Kampung Bakat aims to develop creativity, independence, and economic skills through digital marketing, entrepreneurship training, and the production of trendy beverages for elementary to middle school students in Sukomanunggal, Surabaya. This program was conducted because formal education has not fully accommodated these skills, while children from economically disadvantaged families need early opportunities to practice entrepreneurship. The program methods included socialization, training, application of appropriate technology, and continuous mentoring from May to November 2025. The training covered the development of an entrepreneurial mindset, digital marketing practice, and the creation of healthy and innovative trendy beverages. Results showed improvements in entrepreneurial skills, digital marketing understanding, creativity, teamwork, and self-confidence. Children were able to practice production and sales independently, including during Kampung Bakat Art Performances. Support from parents, KuBA managers, and appropriate technology reinforced practical learning. In conclusion, this mentoring program effectively fosters entrepreneurial spirit, enhances economic skills, and builds participant independence.